Perceptions of Pre-service Science Teachers in Indonesia about the Greenhouse Effect (GHE) - Shelly Efwinda; Abdul Hakim; Nadya Meriza; Aristo Hardinata; Abdul Latip (Jurnal Pendidikan dan Pengajaran, 2024)
Tackling climate change is one of the Sustainable Development Goals (SDGs) and concerns the world community. The greenhouse effect (GHE) is the primary source of global warming and influences climate change. This exploratory research aims to explore the perceptions of pre-service science teachers in Indonesia about the GHE. The study's participants were 265 Indonesian pre-service science teachers. Research data was collected through a questionnaire. The questionnaire consists of three open questions and 36 statements with multiple-choice responses. The open-ended inquiry is coded, and the resume is shown as a mind map. The remaining questionnaire results were examined using descriptive statistics. Based on the analysis results, it can be concluded that most prospective teachers have not been able to describe the process of GHE in detail, and there are still several misperceptions. Prospective teachers must have the correct perception of the topics they will teach their students in the future, so the implications of this research are recommendations for institutions and teaching lecturers in teacher education to discuss GHE topics in more detail and ensure there are no misperceptions.